Quantifying Dispersal in a Metacommunity and Understanding Its Role in Local Community Structure - Sciullo, Luana (My University, 2010)
Dispersal has been long recognized as an important process in metacommunity dynamics, allowing isolated communities to interact with each other through the movement of individuals. Metacommunity theory and its four models (species-sorting, mass-effects, patch-dynamics and neutral) emphasize the significance of dispersal in the structure and composition of local community. Therefore, quantifying movements of individuals between patches is necessary to understand how systems will respond to varying degrees of connectivity and resulting species interactions. Many studies that have attempted to quantify dispersal, particularly of aquatic invertebrates, found conflicting results with respect to the intensity with which dispersal occurs. Moreover, investigations of invertebrate dispersal factors aquatic habitats have neglected to consider the influence of multiple factors such as life cycle stage, species, and external environmental features on dispersal rate via three vectors (wind, overflow, and animal transport). Colonization experiments have largely emphasized the importance of dispersal in influencing species richness, abundance and diversity but have yet to demonstrate direct comparisons between composition of dispersing species and local community structure. I investigated dispersal of aquatic invertebrates in a rock pool metacommunity, its possible influencing factors (species, life stage and the surrounding rock pool environment), and potential impact on species composition in local communities. To explore this, I used a combination of dispersal interception traps, colonization experiments and long tern biotic community surveys. I found dispersal occurs both rapidly and in high abundance across rock pools, particularly using wind and flow vectors, with minimal influence of connectivity, vegetation and ocean on dispersal rate. Although species and life cycle stages were highly variable and differed in their dispersal intensity, a high degree of similarity existed between composition of dispersing species and local community structure. Regional processes (i.e., dispersal), despite its unpredictability, is important for species assemblage and local community composition and necessary in the colonization of newly created habitats.
Keywords: dispersal; vectors; metacommunity; local community; colonization; regional processes; Biology; Biology